PEMANFAATAN TEPUNG DAUN KAYU MANIS (Cinnamomun burmanii) TERHADAP PERTUMBUHAN DAN EFISIENSI PAKAN IKAN SIDAT (Anguilla marmorata) - Sandriyani, Sandriyani; Nasmia, Nasmia; Mangitung, Septina Fifi (FAPETKAN UNTAD, 2017)
The research was conducted in June 2016 and housed at Fish Seed (BBI) Tulo, Central Sulawesi province. Test organisms used were seeds of African catfish (Clarias gariepinus), totaling 180 fishs. Research procedure includes the preparation of tools and materials, making the seeds, water quality measurements, anesthesia with ice cubes, transportation activities for 4-5 hours and data collection. The study design research is completely randomized design (CRD) consisting of 3 treatments and 5 replications. The results showed that the different temperature levels in closed transport no significant effect (P> 0.05) on survival rate seed catfish. The average value of the highest survival rate 76% was obtained in treatment A (temperature 12OC.Water quality in the maintenance of media contained within the range that can be tolerated.